2020
DOI: 10.1007/s10111-020-00628-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of training on truck drivers’ interaction with cyclists in a right turn

Abstract: With encounters between trucks and cyclists still being a major safety issue and physical as well as technological improvements far from ubiquitous implementation, training truck drivers in anticipatory driving to improve their interaction with cyclists may be a way forward. After a baseline drive in an urban environment, truck drivers inexperienced with urban driving received a dedicated training on anticipatory driving, followed by another drive along the same route several weeks later. The drivers were also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 27 publications
(30 reference statements)
0
8
0
Order By: Relevance
“…The last metric identified from the literature related to monitoring visual behavior is the first fixation duration, which means how long the first fixation lasts. Gaze Location [10,12,[22][23][24][25] Pupil Dilation [11] Fixation Duration [4,13,15,[18][19][20][21][22]26] Fixation Frequency [4,13,14,16,18,19,21,25] Saccade Duration [4,13,20] Saccade Frequency [14][15][16]19] Total Recording Duration [19,26] First Fixation Duration [15] 1.…”
Section: Application Of Eye-tracking Technologymentioning
confidence: 99%
See 2 more Smart Citations
“…The last metric identified from the literature related to monitoring visual behavior is the first fixation duration, which means how long the first fixation lasts. Gaze Location [10,12,[22][23][24][25] Pupil Dilation [11] Fixation Duration [4,13,15,[18][19][20][21][22]26] Fixation Frequency [4,13,14,16,18,19,21,25] Saccade Duration [4,13,20] Saccade Frequency [14][15][16]19] Total Recording Duration [19,26] First Fixation Duration [15] 1.…”
Section: Application Of Eye-tracking Technologymentioning
confidence: 99%
“…Additionally, drivers have a broader spatial distribution of eye fixation during a call. Kircher et al [ 14 ] performed another study to evaluate the performance of truck drivers after receiving training, and the recorded visual behavior by a head-mounted eye-tracker showed that the truck drivers paid more attention to cyclists after receiving the training and had much better speed management. Besides driving safety, workers’ attentional behavior toward safety problems on construction sites was also highly related to their personality, according to the study through tracking workers’ visual behavior by Hasanzadeh et al [ 15 ], it showed that those who were introverted, conscientious, and open to experience could respond to hazardous areas more efficiently.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors describe typical ways of how an HGV-VRU turning/crossing scenario might unfold depending on various situational aspects (e.g., road user trajectories, infrastructure layout, traffic control devices, presence of other traffic), and where the interaction ends with “either the truck or cyclist going first”. In another study with a similar methodology ( Kircher et al, 2020 ), improved driver behavior from before and after training could be observed, such as better speed management, strategic/tactical positioning strategies, and more intensive monitoring of cyclists. The authors state that adopting such anticipatory driving techniques can improve interactions with VRUs.…”
Section: Resultsmentioning
confidence: 99%
“…Three other implicit cues that we identified reflect communication via movements and proximity (kinesics and proxemics): pedestrians accepting a gap and deciding to cross the street ( Petzoldt et al, 2017 ), an HGV driver considerably reducing the speed when encountering a VRU to signal his/her willingness to give way ( Schindler and Bianchi Piccinini, 2021 ), and cyclists dismounting their cycles to get priority at a zebra crossing ( Pokorny and Pitera, 2019 ). The rest of the implicit cues reflect a combination of eye/body language (oculesics/kinesics) (an HGV driver or cyclist directs his/her head and glances towards the interacting partner to get perception of the situation and possibly to signal a request for movement or perception, Kircher and Ahlström (2020) , Kircher et al (2020) , Richter and Sachs (2017) , and Schindler and Bianchi Piccinini (2021) ), and a combination of kinesics, proxemics and chronemics [an HGV approaching a cyclist and choosing to remain behind in order to leave the opportunity for the cyclists to cross first, Kircher and Ahlström (2020) ]. When it comes to the more explicit communication cues that we identified, one of them reflects selecting a strategic position (proxemics) to request perception: a cyclist stops earlier and more to the left in the lane to avoid blind-spots around the HGV and thereby enable the HGV driver to perceive him/her ( Thorslund and Lindström, 2020 ).…”
Section: Resultsmentioning
confidence: 99%